In/Exclusion in the Clinic: Down's Syndrome, Dysmorphology and the Ethics of Everyday Medical Work. (October 2015) - Thomas, Gareth M; Latimer, Joanna
In this article, we draw on two clinical ethnographies to explore how mundane social practices, affective processes and cultural materials (re)produce divisions and forms of in/exclusion. By treating everyday life and routines as serious categories of analysis, we identify how power relations are accomplished and how persons/future persons – namely the 'dysmorphic' child or the foetus who has or may have Down's syndrome – are constituted as un/valued or in/excluded. In relation to dysmorphology, we show how the living dysmorphic child is given shelter but future reproductions of such children are enacted negatively and as to be avoided. With reference to Down's syndrome, we capture how the condition is made absent in the antenatal clinic and constituted as a negative outcome. In sum, we recognise how exploring the micro and everyday reveals who/what is valued and how particular ways of being in the world are threatened, denied or effaced.